PENINGKATAN KEMAMPUAN VISUAL SPASIAL MELALUI MODEL SENTRA BALOK DI KELOMPOK B TK MAPPADAELO KECAMATAN AWANGPONE KABUPATEN BONE - INTAN NURAINI; Bonita Mahmud; Fitrya Ali Imran (EDUCHILD (Journal of Early Childhood Education), 2026)
Abstract This study aims to: 1) To determine the increase in visual spatial abilities in children before and after the application of the block center model in group B of Mappadaelo Kindergarten, Lattekko Village, Awangpone District, Bone Regency. 2) To determine the application of the block center model in improving visual spatial abilities in children in group B of Mappadaelo Kindergarten, Lattekko Village, Awangpone District, Bone Regency. The type of research used by the author in this study is quantitative research with the Pre-Experimental research method with one group pretest and posttest type conducted at Mappadaelo Kindergarten, Lattekko Village, Awangpone District, Bone Regency with a total of 10 children. The data usage technique uses observation and tests related to the research. The results of the data obtained during the research were analyzed using the SPSS application for Windows version 27, to determine the results of the descriptive statistical calculations of the pretest-posttest, Paired Sample T-Test Statistics. The results of the study indicate that spatial visual abilities can be increased through the use of the Block Center Model in children aged 5-6 years in Mappadaelo Kindergarten. The application of the block center model is carried out with two activities, namely role playing with blocks and building 3D constructions by looking at pictures. Based on the results of the Paired Sample T-Test Statistics on the pretest and posttest, it can be seen (Sig. (2-tailed) = 0.000 <0.05, and t count 7.357> t table = 3.536), then H1 is accepted and H0 is rejected. Because the significance value obtained is 0.000, so it can be said that children's spatial visual abilities can be increased through the block center model in group B of Mappadaelo Kindergarten, Lattekko Village. Keywords: Block Center Model, Visual Spatial Ability, Early Childhood